ANALGESIC, ANTI-INFLAMMATORY, ANTIPYRETIC EVALUATION OF ETHANOLIC EXTRACT OF LEAF OF POLYALTHIA LONGIFOLIA - S, Ramjith.U.; Salim, Faby; S, Ashamol.K.; Jacob, Cyril Mathews (Journal of Biomedical and Pharmaceutical Research, 2021)
Polyalthia longifolia leaves ethanolic extracts produced significant analgesic activity in both Hot plate and acetic acid induced writhing models in mice. In hot plate method percentage increase in reaction time was determined where as in acetic acid induced writhing model percentage decrease in writhings was determined. From the results obtained it can be concluded that Polyalthia longifolia leaves has analgesic, anti inflammatory and antipyretic activity. Keywords: Analgesic, Anti-inflammatory, Antipyretic, Hot plate method, Acetic acid induced writhing model.